2021
DOI: 10.3390/foods10112786
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Domestic Cooking on Quality, Nutrients and Bioactive Substances of Undaria pinnatifida

Abstract: Undaria pinnatifida (UP) is a brown algae commonly consumed as food in Asian countries. The purpose of this study was to compare the effects of different domestic cooking methods (i.e., air frying (AF), microwaving, and high temperature and pressure (HTP) cooking) on the nutritional and bioactive substances in UP, as well as on UP color and texture, in order to identify methods to retain beneficial components better. In this study, microwave treatment resulted in better retention of color, polysaccharide (4.17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It is commonly recognised that UP is a great source of numerous common nutrients, including vitamins, minerals, and dietary fibre. A range of bioactive substances with anti‐inflammatory, anti‐tumour, anti‐thrombotic, and immunomodulatory qualities are also present in UP (Jiang et al ., 2021). In addition, UP is an important source of carbohydrate‐based hydrocolloids, such as alginates, carrageenan, and agar.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly recognised that UP is a great source of numerous common nutrients, including vitamins, minerals, and dietary fibre. A range of bioactive substances with anti‐inflammatory, anti‐tumour, anti‐thrombotic, and immunomodulatory qualities are also present in UP (Jiang et al ., 2021). In addition, UP is an important source of carbohydrate‐based hydrocolloids, such as alginates, carrageenan, and agar.…”
Section: Introductionmentioning
confidence: 99%
“…They are also attracting attention as a valuable source of functional ingredients in the nutritional, medical and cosmetic industries ( Park & Lee, 2021 ). Based on their chemical makeup, seaweeds are divided into green, brown, and red seaweed, with brown seaweed being the most popular for human consumption ( Jiang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Jiang Shan et al [ 18 ] studied the effects of traditional cooking methods (blanching, steaming, boiling, and baking) on the color, texture, and bioactive nutrient content of Undaria pinnatifida ( U. pinnatifida ), and the results showed that blanching and boiling were more beneficial than other cooking methods in maintaining the quality of U. pinnatifida . In addition, Jiang Shan et al [ 19 ] further investigated the effects of domestic cooking methods (air frying (AF), microwave, and high-temperature and -pressure (HTP) cooking) on the quality, nutrient content, and bioactive substances of U. pinnatifida , and the results showed that of the three processing methods, microwave cooking had a more favorable effect in maintaining the quality of U. pinnatifida . Akomea-Frempong et al [ 20 ] reported on the effects of blanching, freezing, and fermentation on the physicochemical, microbiological, and organoleptic quality of sugar kelp ( Saccharina latissima ).…”
Section: Introductionmentioning
confidence: 99%